DNA Isolation on Captive Sumatran Elephant in Elephant Training Center, Way Kambas National Park: A First Step towards Its ID Card - Elly L. Rustiati; Priyambodo Priyambodo; Siti Asiyah; Dedi Candra; Diah E. Anggraini; Elizabeth D. Krismuniarti; Eko Agus Srihanto; Liza Angeliya; Nuning Nurcahyani; Enny Saswiyanti (The International Journal of Tropical Veterinary and Biomedical Research, 2018)
Elephant Training Center (ETC) Way Kambas National Park (WKNP) was built to support human-elephantmitigation conflict. The small population of captive sumatran elephant in ETC WKNP need a comprehensivestrategy in order to maintain the genetic variation of each individual and avoid inbreeding drive. Currently, geneticstudies have opened new field studies in ecology, included conservation ecology. Patterns in variation of populationhas been investigated by molecular method supporting species conservation effort. The captive sumatran elephant’sID Card is a necessary in database building, which included morphology, health status, and genetic profile. Geneticprofile in each ID Card was filled by cytogenetic and molecular profile for RADP result, that initiated with DNAisolation. The DNA sources collected by blood sampling protocol described by Asiyah et al. (2016) from captivesumatran elephant in ETC, WKNP, and be carried to laboratory in cold condition. The DNA sources stored at 4oCand isolated following commercial protocol. The result of DNA isolation stored at -20oC until amplificationanalysis. DNA isolation was successfully done, for further individual genetic ID building.